Ball-grip exercise to improve fine motor function in a patient with non-hemorrhagic stroke: A nursing case study - Diski, Diski; Romadhon, Muhammad; Saputra, Andre Utama; Rimbawati, Yazika (School of Health Sciences Al-Ma'arif, 2026)
Background: Non-hemorrhagic stroke frequently results in upper extremity motor impairment, which limits patients’ functional independence and quality of daily living. Fine motor dysfunction commonly occurs due to neuromuscular damage affecting coordination and muscle strength. Rehabilitation interventions that are simple, accessible, and feasible in nursing practice are essential to support early motor recovery. Ball-grip exercise represents a low-cost rehabilitative approach that may enhance muscle strength through repetitive hand stimulation. Objective: This study aimed to analyze the effect of ball-grip exercise on improving fine motor function in a patient with non-hemorrhagic stroke through a nursing case study approach. Methods: A descriptive case study design was conducted at Bhayangkara Moh. Hasan Hospital Palembang in June 2025. Two adult patients diagnosed with non-hemorrhagic stroke were selected using purposive sampling based on upper limb weakness, stable consciousness, communication ability, and willingness to participate. The intervention consisted of ball-grip exercise performed for 10–15 minutes twice daily over four consecutive days alongside standard pharmacological therapy. Muscle strength was assessed using Manual Muscle Testing (MMT), supported by observation, interviews, physical examination, and medical record documentation. Data were analyzed descriptively by comparing pre- and post-intervention motor function. Results: The patient receiving combined pharmacological therapy and ball-grip exercise demonstrated improvement in muscle strength from MMT score 3 to 4 within four days, accompanied by increased functional independence, particularly in holding a spoon and eating independently. Conversely, the patient receiving pharmacological therapy alone showed no significant improvement in muscle strength or fine motor function during the same observation period. These findings indicate that ball-grip exercise may accelerate fine motor recovery in patients with non-hemorrhagic stroke. Conclusion: Ball-grip exercise is a practical and feasible nursing rehabilitation intervention that may enhance fine motor recovery in non-hemorrhagic stroke patients. Integration of simple rehabilitative exercises with pharmacological therapy may optimize functional outcomes. Healthcare providers are encouraged to incorporate structured hand exercises into routine nursing care, and further research with larger samples and longer observation periods is recommended to strengthen clinical evidence.